Perspectives of Male Lecturers on Women (Wives) Working in the Public Sphere - Yurisna Tanjung; Ishomuddin Ishomuddin; Wahyudi Wahyudi; Arifin Saleh (International Journal Reglement & Society (IJRS), 2023)
The public space and new institutions that emerged and developed within the reformed state institutions became a space for women to access women's representation and involvement which resulted in public policies that were considered important and a priority in the women's movement. Public policy has different impacts on men and women. In addition, public policy also has the capacity to both perpetuate and eliminate gender discrimination and injustice. The study entitled perspectives of male lecturers on women (wives) working in the public Sphere is to describe men's perspectives on women who work in the public sphere. The research method used in this study is qualitative in order to interpret how the perspective of male lecturers towards women who work in public spaces and whether male lecturers who have wives work in the public area provide room for negotiation in the distribution of household roles. The results of the study show that women as wives and workers in the public sphere represent a practice of the Muslim feminist movement which chooses to work not only because it fulfils the economic needs of the family, but also shows the growing awareness of their rights as a form of self-existence and their potential